2010
DOI: 10.1021/bm100738r
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Disordered Mollusk Shell Prismatic Protein That Modulates Calcium Carbonate Crystal Growth

Abstract: The formation of calcite prism architecture in the prismatic layer of the mollusk shell involves the participation of a number of different proteins. One protein family, Asprich, has been identified as a participant in amorphous calcium carbonate stabilization and calcite architecture in the prismatic layer of the mollusk, Atrina rigida . However, the functional role(s) of this protein family are not fully understood due to the fact that insufficient quantities of these proteins are available for experimentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 42 publications
(205 reference statements)
4
64
0
1
Order By: Relevance
“…In the sea urchin spicule, the SM50 matrix protein found in the larval spicule is found to have domains with repeats of glycine, proline and asparagine [29]. This differs with the repetitive domains found in mollusk shell extracellular proteins, which have long repeats of aspartic acid interspersed by a repeat block of valine, alanine, and glutamic acid [24]. It has been thought that these domains found in these proteins are themselves switches which are necessary for structural conformations that are responsible for specific Ca 2þ mineral ion affinities [30].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the sea urchin spicule, the SM50 matrix protein found in the larval spicule is found to have domains with repeats of glycine, proline and asparagine [29]. This differs with the repetitive domains found in mollusk shell extracellular proteins, which have long repeats of aspartic acid interspersed by a repeat block of valine, alanine, and glutamic acid [24]. It has been thought that these domains found in these proteins are themselves switches which are necessary for structural conformations that are responsible for specific Ca 2þ mineral ion affinities [30].…”
Section: Introductionmentioning
confidence: 83%
“…The exact roles of these macromolecules are still unknown while what is known, is that this fraction is necessary for normal mineralized tissue growth and development, as well as its materials properties [19][20][21][22]. There are no consistent compositions or structural homologs found amongst these organic fractions, except that they do have regions which are highly repetitive and have characteristics of "intrinsically disordered protein" (IDP) domains, domains implicated in either mineral binding or the assembly process [23][24][25]. Many have associated these IDPs to being active participants in various biological processes like biomineralization [24,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammals DMP1 4.0 CD, DLS, FTIR, SAXS (Gericke et al, 2010;He et al, 2003aHe et al, , 2003b DPP 2.8 CD, NMR, SAXS (Cross et al, 2005;Evans et al, 1994;Fujisawa & Kuboki, 1998;George & Hao, 2005;He et al, 2005b;Lee et al, 1977) BSP 4.1 CD, NMR, SAXS (Fisher et al, 2001;Tye et al, 2003Tye et al, , 2005Wuttke et al, 2001) OPN 4.4 CD, NMR, FTIR (Fisher et al, 2001;Gorski et al, 1995) amelogenin 6.6 CD, NMR (Buchko et al, 2010;Delak et al, 2009b;Ndao et al, 2011;Shaw et al, 2008) statherin 8.0 CD, NMR (Long et al, 2001;Naganagowda et al, 1998;Raj et al, 1992) lithostathine 5.7 CD (Gerbaud et al, 2000) Haliotis rufescens AP7 5.2 CD, NMR (Kim et al, 2004(Kim et al, , 2006aMichenfelder et al, 2003;Wustman et al, 2004) Atrina rigita Asprich 2.7-3.5 CD, NMR (Collino et al, 2006;Delak et al, 2009aDelak et al, , 2008Kim et al, 2008;Ndao et al, 2010) Procambrus clarkii CAP-1 3.9 CD (Inoue et al, 2007) Strongylocentrotus purpuratus SM50 10.8 CD, NMR (Xu & Evans, 1999;Zhang et al, 2000) PM27 8.1 CD, NMR Danio rerio Stm 4.1 CD, gel filtration (Kaplon et al, 2008(Kaplon et al, , 2009 Table 1. IDPs involved in biomineralization of calcium carbonate and phosphate for which a disordered structure has been confirmed...…”
Section: Protein Pi Methods Referencementioning
confidence: 99%
“…Furthermore, they showed that a part of Ca 2+ ions forms neutral equilibrium clusters before nucleation of the supersaturated solution arises (18). Several groups have also investigated the influence of different additives on the nucleation of CaCO 3 (19)(20)(21)(22). Amongst others, polycarboxylates which usually serve as inhibitors of the formation of scale in laundry detergents or dishwaters were used to investigation inhibition of nucleation (23).…”
Section: Introductionmentioning
confidence: 99%